Antilocality at the Phase Edge. (23rd August 2021) - Zyman, Erik
Abstract: Much work has argued that syntactic movement is subject to antilocality constraints that prevent it from being too short. If so, a crucial question is precisely what those constraints are. This article investigates the interaction between antilocality and phases, and it argues that antilocality manifests in a particular way at phase edges. The article defends a generalization dubbed Phasal Antilocality: for a phase YP, movement from within a constituent at the edge of YP must cross an XP dominating YP. It is shown that Phasal Antilocality, together with other ingredients, explains the intricate generalizations about when PP extraction is and is not possible from subjects. The analysis also correctly predicts that violations resulting from illicit PP extractions from subjects should be ameliorated under a wide range of circumstances. Finally, the article considers a possible deduction of Phasal Antilocality effects from Last Resort, the need for Merge to immediately satisfy a previously unsatisfiable feature.